Terrain slope classes and potential for mechanization to coffee plantation in the state of Paraná - Höfig, Pedro; Araujo-Junior, Cezar Francisco (Coffee Science - ISSN 1984-3909, 2015)
The soil slope is one of the most soil geomorphological properties limiting the use of agricultural machinery. Thus, the aim of this study was to analyze the slope terrain in the state of Paraná and classify them as the potential for mechanization. The area covered by the study comprises all recommended the cultivation of coffee in the State of Paraná area comprising the coordinates of the southern latitudes 22º 51’ 50 “to 24º 76’ 70” west longitude and 49º 55’ 30” to 54º 34’ 20” from Greenwich. In this area, slope maps (clinographic maps) of land were developed through GIS techniques. The analysis of soil slope was elaborated from the slope satellite images acquired by the by the Shuttle Radar Topography Mission - SRTM, NASA, with a spatial resolution of 90 m. These images were imported into ArcGIS® 10 and slope soil maps were generated from the tool slope. The mesoregions of the State of Paraná were divided into: Northwest, Central North, Old North, Western Center and West. The soil slope classes were classified according to the potential for mechanization in extremely able (0 to 5 %), very able (5.1 to 10 %), able (10.1 to 15 %), moderately able (15.1 -20 %) and not recommended (> 20 %). Our results showed that the total indicated by the Climatic Zoning of the State of Parana for the cultivation of coffee, 89 % of the land area are not limiting to mechanization by the criterion of soil slope classes. Among of the regions, the Northwest is the one with the greatest potential for mechanization of coffee. On the other hand, the Northern Pioneer mesoregion, which concentrates 37 % of coffee plantations in the State of Paraná, there are 10 % of the area not recommended for mechanization based on slope, which represents an area of 160,000 hectares. Therefore, the low adoption to mechanized in coffee plantations in the State of Paraná is not due limitations imposed by the slope on mechanization.